Lightweight, thermally insulating, and low dielectric microcellular high-impact polystyrene (HIPS) foams fabricated by high-pressure foam injection molding with mold opening. Issue 45 (2nd November 2018) - Wang, Guilong; Zhao, Guoqun; Dong, Guiwei; Song, Libin; Park, Chul B.
Abstract : Lightweight, thermally insulating, and low dielectric microcellular high-impact polystyrene (HIPS) foams were fabricated by high-pressure foam injection molding with mold opening. Abstract : In this study, we used a high-pressure foam injection molding process to fabricate microcellular high-impact polystyrene (HIPS) foams with a tailored cellular structure. The process is cost-effective, highly efficient and flexible, and can be easily scaled up to complex components. The cellular structure of HIPS foam can be tuned over a wide range by manipulating packing time, cooling time, mold temperature, and mold-opening distance. Microcellular HIPS foam with a weight reduction of up to 60% was prepared, which possesses a low thermal conductivity of 60 mW m −1 K −1 and an ultra-low dielectric constant of 1.25. Both the thermal conductivity and the dielectric constant can be tailored by regulating the expansion ratio of HIPS foam. Mathematical models based on the mixing rule were developed to clarify the dependence of thermal conductivity and dielectric constant on the cellular structure of the foam. The outstanding thermally and electrically insulating properties of HIPS foams come from a large amount of air in the microcellular structure. These lightweight, thermally insulating, and ultralow dielectric microcellular HIPS foams hold great promise as an ultra-efficient insulating material for future use in many applications such as microelectronics and microelectromechanical systems (MEMSs).